Increased auctioning in the EU ETS and trade in guarantees of origin for renewables: a comparison of the impact on power sector producer rents - Mario Ragwitz; Gustav Resch; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2007)
The European Commission is currently reviewing two major policy instruments which will pose major economic challenges and opportunities for EU power producers. First, the European Emissions Trading Scheme (EU ETS) is likely to include a high percentage of auctioning. Second, support schemes for electricity from renewable energy sources may involve open private-actor trade of guarantees of origins (GO). This paper provides a first coarse comparison of the impacts of these policy changes on power sector producer rents. The results suggest that the losses in producer rents from increased auctioning in the EU ETS may be offset by additional producer rents from private-actor based GO trade for renewable electricity.
urn:nbn:de:0011-n-685965
Keywords: 330; Emissionshandel; Förderung regenerativer Energien; Auktion; Kapazitätsauslastung; Rententheorie; Elektrizitätswirtschaft; EU-Staaten